Analisis Leader Member Exchange, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Manajerial - Asdani, Andi; Handayawati, Kuni Utami (STIE Malangkucecwara, 2019)
Every organization (including those in tertiary institutions) who wish to persist in being a part of an increasingly competitive environment, must be supported by strong, powerful and high-performing human resources. This would include leaders who are able to direct their employees to achieve organizational goals. Therefore, management needs to pay great attention in realizing a strong organizational culture and applying the LMX theory in order to make the work atmosphere more pleasant and being able to use it as a